2019
DOI: 10.1016/j.syapm.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

A new symbiotic nanoarchaeote (Candidatus Nanoclepta minutus) and its host (Zestosphaera tikiterensis gen. nov., sp. nov.) from a New Zealand hot spring

Abstract: Three thermophilic Nanoarchaeota-Crenarchaeota symbiotic systems have been described. We obtained another stable anaerobic enrichment culture at 80°C, pH 6.0 from a New Zealand hot spring. The nanoarchaeote (Ncl-1) and its host (NZ3) were isolated in co-culture and their genomes assembled. The small (∼200nm) flagellated cocci were often attached to larger cocci. Based on 16S rRNA gene similarity (88.4%) and average amino acid identity (52%), Ncl-1 is closely related to Candidatus Nanopusillus acidilobi. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 103 publications
3
55
0
Order By: Relevance
“…On the other hand, these two tightly associated species do not appear to be involved in rampant gene exchange. Unlike acidophilic members of DPANN superphylum, which have several clusters of orthologous genes shared between the ectosymbiont and the host 24,34 , the nanohaloarchaeal genome shows no synteny with the host genome except for the ancestrally collinear loci coding for ribosomal proteins, suggesting no recent transfer of chromosomal fragments between the two (Supplementary Fig. 9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, these two tightly associated species do not appear to be involved in rampant gene exchange. Unlike acidophilic members of DPANN superphylum, which have several clusters of orthologous genes shared between the ectosymbiont and the host 24,34 , the nanohaloarchaeal genome shows no synteny with the host genome except for the ancestrally collinear loci coding for ribosomal proteins, suggesting no recent transfer of chromosomal fragments between the two (Supplementary Fig. 9).…”
Section: Resultsmentioning
confidence: 99%
“…To date, few finished genome sequences are available for the representatives of DPANN superphylum, and difficulties in their cultivation prevented proper characterization of their growth requirements, morphology and physiology. Only ectosymbiotic and ectoparasitic thermophiles from the candidate phylum Nanoarchaeota and acidophiles from the candidate phylum Micrarchaeota have been obtained in stable binary co-cultures with their hosts from the phyla Crenarchaeota and Euryachaeota, respectively 21-24 . Most recently, the study of enrichment cultures containing members of nanohaloarchaea ( Ca .…”
Section: Introductionmentioning
confidence: 99%
“…The dilution-to-extinction approach, followed by filtration and coculture reconstruction, was recently successfully applied for isolation of the nanoarchaeon Ca. Nanoclepta minutus with its host, the thermophilic crenarchaeon Zestosphaera tikiterensis (27). Here, we applied a similar strategy and obtained a binary culture of a nanohaloarchaeon, Ca.…”
Section: Discussionmentioning
confidence: 99%
“…These include two MAGs related to Acidilobus saccharovorans (each with 81% RpoB amino acid identity), a MAG related to Thermogladius calderae (87% ID), a MAG related to Thermoproteusuzoniensis (97% ID), a MAG related to Caldivirga maquilingensis (94% ID), a MAG related to Pyrobaculum aerophilum (92% ID), a MAG related to Thermofilum carboxydotrophus (100% ID), a MAG related to Vulcanisaeta distributa (93% ID), two MAGs related to Fervidicoccus fontis (71% and 79% ID), a MAG related to Thermocrinis ruber (98% ID) and a Thaumarchaeote‐associated MAG (Supporting Information Appendix S1). Further, a divergent MAG that is distantly related to a S 2 O 3 2− reducing Desulfurococcales strain (e.g., 63% ID to Zestosphaera tikiterensis (St. John et al ., )) was identified that exhibited the metabolic potential for anaerobic S° reduction.…”
Section: Resultsmentioning
confidence: 99%